Association of weight changes with SARS-CoV-2 infection and severe COVID-19 outcomes: A nationwide retrospective cohort study - Sung Soo Yoon; Yohwan Lim; Seogsong Jeong; Hyun Wook Han (Elsevier, 2023)
Background: Obesity is a risk factor for COVID-19. However, it is unknown whether weight changes can alter this risk. We investigated the association of weight changes with SARS-CoV-2 infection and acute severe COVID-19 outcomes occurring within two months of the infection. Methods: We used 6.3 million nationwide cohort. The body weight was classified as follows: (1) underweight, body mass index (BMI) < 18.5 kg/m2; (2) normal, BMI 18.5-22.9 kg/m2; (3) overweight, BMI 23-24.9 kg/m2; (4) obese, BMI≥ 25 kg/m2. Weight changes were defined by comparing the classification of body weight during the health screening period I and II. The outcomes were SARS-CoV-2 infection and severe COVID-19 outcomes within two months after the infection. The association was evaluated using multivariable-adjusted logistic regression. The following covariates were adjusted: age, sex, household income, cigarette smoking, alcohol consumption, physical activity, hypertension, diabetes mellitus, dyslipidemia, Charlson comorbidity index score, and dose of all COVID-19 vaccinations prior to SARS-CoV-2 infection. Results: Of the 2119,460 study participants, 184,204 were infected with SARS-CoV-2. Weight gain showed a higher risk of SARS-CoV-2 infection in underweight to normal and normal to overweight groups. Conversely, weight loss showed a lower risk of SARS-CoV-2 infection in normal to underweight, overweight to underweight, overweight to normal, obese to normal, and obese to overweight groups. In addition, weight gain revealed a higher risk of severe COVID-19 outcomes, whereas weight loss showed a lower risk of severe COVID-19 outcomes. Conclusion: This study found that weight loss and gain are associated with a lower and higher risk of both SARS-CoV-2 infection and severe COVID-19 outcomes, respectively. Healthy weight management may be beneficial against the risk of COVID-19.